Helicobacter pylori vacA genotypes and cagA gene in a series of 383 H. pylori-positive patients - Rudi, Jochen; Kuck, Dirk; Rudy, A.; Sieg, A.; Maiwald, Matthias; Stremmel, Wolfgang (Zeitschrift für Gastroenterologie, 2000)
Thieme E-Books & E-Journals
Gesehen am 19.11.2021